Problems of Filipino college students - Guillermo, Virginia D.
Filipino college student tends to be faced with problems related to his family, school and community taken all together.
"Study shows similarities in problems of students in public and private colleges."
Keywords: College students -- Philippines -- Social conditions; College students -- Philippines -- Attitudes